Symptom clusters in inflammatory bowel disease: a scoping review - Xu, Keying; Li, Mengjiao; Jiang, Ping (Frontiers in Medicine, 2025)
BackgroundInflammatory bowel disease (IBD) is a chronic relapsing gastrointestinal disorder with a high symptom burden. Patients often report multiple concurrent symptoms, yet most studies have examined them individually. Symptom clusters—defined as groups of co-occurring and interrelated symptoms—provide a framework for understanding this complexity. Evidence on IBD-specific clusters, however, remains fragmented and inconsistent.MethodsWe conducted a scoping review following Arksey and O'Malley's framework to synthesize findings on IBD symptom cluster types, assessment instruments, associated factors, and dynamic trajectories. Searches covered database inception through 31 October 2024.ResultsThirteen studies were included, identifying 29 symptom clusters. Marked heterogeneity and overlap were observed. To integrate findings, clusters were categorized into five groups: gastrointestinal/physical, psychological, systemic/fatigue, nutritional/appetite-related, and mixed/trajectory-related. Assessment instruments varied considerably, most lacking IBD-specific validation. Reported associated factors included demographic, clinical, and treatment variables, but results were inconsistent. Few studies addressed longitudinal changes or interactions among clusters.ConclusionResearch on IBD symptom clusters remains limited and heterogeneous. Standardized definitions and validated tools are urgently needed. Most existing studies did not stratify findings by disease subtype, although limited evidence indicates that UC and CD appear to exhibit distinct clustering patterns. Future studies should adopt longitudinal and biomarker-informed designs, and examine interactions among clusters, to improve clinical management and patient outcomes.